Standardised clinical data from patients with primary ciliary dyskinesia: FOLLOW-PCD. Issue 1 (10th February 2020) - Goutaki, Myrofora; Papon, Jean-François; Boon, Mieke; Casaulta, Carmen; Eber, Ernst; Escudier, Estelle; Halbeisen, Florian S.; Harris, Amanda; Hogg, Claire; Honore, Isabelle; Jung, Andreas; Karadag, Bulent; et al.
Clinical data on primary ciliary dyskinesia (PCD) are limited, heterogeneous and mostly derived from retrospective chart reviews, leading to missing data and unreliable symptoms and results of physical examinations. We need standardised prospective data collection to study phenotypes, severity and prognosis and improve standards of care. A large, international and multidisciplinary group of PCD experts developed FOLLOW-PCD, a standardised clinical PCD form and patient questionnaire. We identified existing forms for clinical data collection via the Better Experimental Approaches to Treat PCD (BEAT-PCD) COST Action network and a literature review. We selected and revised the content items with the working group and patient representatives. We then revised several drafts in an adapted Delphi process, refining the content and structure. FOLLOW-PCD has a modular structure, to allow flexible use based on local practice and research focus. It includes patient-completed versions for the modules on symptoms and lifestyle. The form allows a comprehensive standardised clinical assessment at baseline and for annual reviews and a short documentation for routine follow-up. It can either be completed using printable paper forms or using an online REDCap database. Data collected in FOLLOW-PCD version 1.0 is available in real-time for national and international monitoring and research. The form will be adapted in the future after extensive piloting in different settings and we encourage the translation of the patient questionnaires to multiple languages. FOLLOW-PCD will facilitate quality research based on prospective standardised data from routine care, which can be pooled between centres, to provide first-line and real-time evidence for clinical decision-making. Standardised follow-up of PCD patients enables quality research with real-time data from routine care, providing evidence for clinical decision-making http://bit.ly/2PDfISF